(untitled) (Research, Society and Development, 2025)
The aging of the world’s population is increasing every day, and one of the consequences of this increase is falls, which often limit these individuals in their daily activities. Physiotherapy contributes to this by using techniques and rehabilitation programs to promote fall prevention, especially in the elderly. The aim of this article was to analyze the role of physical therapy in preventing falls in the elderly, identifying strategies, therapeutic resources, and outcomes described in the literature. An integrative review was conducted in national and international databases, including articles published in the last five years. Studies addressing physical therapy interventions for fall prevention were included, totaling 09 publications after applying eligibility criteria. Results showed that multicomponent exercise programs, combining strength, balance training, endurance, and functional mobility, were more effective compared to isolated approaches. Multifactorial strategies, combined with environmental adaptations and educational guidance, also enhanced adherence and benefits. Early hospital-based interventions proved effective in reducing post-discharge functional decline and the risk of subsequent falls. It is concluded that physical therapy is essential for promoting autonomy and quality of life in older adults, providing continuous and individualized prevention capable of significantly reducing fall occurrence.